2013
DOI: 10.1086/670225
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of N95 Filtering Facepiece Respirators with Viable H1N1 Influenza Aerosols

Abstract: OBJECTIVE. Specification of appropriate personal protective equipment for respiratory protection against influenza is somewhat controversial. In a clinical environment, N95 filtering facepiece respirators (FFRs) are often recommended for respiratory protection against infectious aerosols. This study evaluates the ability of N95 FFRs to capture viable H1N1 influenza aerosols. METHODs. Five N95 FFR models were challenged with aerosolized viable H1N1 influenza and inert polystyrene latex particles at continuous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…The reduction of viable H1N1 influenza conferred by five brands of N95 face mask was found to range from 96.3% to 99.995% by Harnish et al (30). The nearly three log 10 reduction in penetration of viruses observed in the current study and in other studies using N95 face masks represents an improvement over the 2.8-fold reduction in penetration of genomic copies for influenza virus challenged via a fine (<5 μm) aerosol obtained during testing of a surgical mask (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of viable H1N1 influenza conferred by five brands of N95 face mask was found to range from 96.3% to 99.995% by Harnish et al (30). The nearly three log 10 reduction in penetration of viruses observed in the current study and in other studies using N95 face masks represents an improvement over the 2.8-fold reduction in penetration of genomic copies for influenza virus challenged via a fine (<5 μm) aerosol obtained during testing of a surgical mask (25).…”
Section: Discussionmentioning
confidence: 99%
“…Any increased benefits of N95 facepiece respirators such as the test mask over surgical masks are likely dependent upon the ergonomic fit of the mask to the wearer's face. This is because in the absence of a tight fit, inward leakage would be expected to dominate over filter penetration as the predominant mode of entry of particulates/aerosols containing infectious agents into the mask, regardless of the type of mask (30)(31)(32)41). A controlled clinical study failed, however, to reveal a significant difference in protection of healthcare workers using fit-tested vs. nonfit-tested N95 masks (42).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement to incorporate such technologies in future standards (for example, Project BREATHE's B95 standard) is being debated. Research has been conducted on facemasks with integrated antimicrobial technology, and the FDA has cleared a few antimicrobial FFRs . Research has also examined the efficacy of chemical and energetic methods to decontaminate FFRs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in various workplaces have demonstrated that fit‐tested FFRs, when used in a complete respiratory protection program, are effective at reducing inhalation exposures, whereas SMs are far less effective for this purpose because of their poorer fit and filtration performance . Laboratory studies have demonstrated the superior filter performance of FFRs over SMs by using various simulants for respiratory pathogens …”
Section: Introductionmentioning
confidence: 99%
“…Each had an effective diameter of 40 mm and a filtration area of 12.6 cm 2 . The sampling flow rate of the pump was 6.3 L/min, which produced the desired face velocity …”
Section: Methodsmentioning
confidence: 99%